Упростите выражения 1) 5а(2-а)-(а+5)^2 2) 3с(с+2)-(с+3)^2 3) (а-6)^2-3а(4а-5) 4) (2х-3)^2-5х(6х-7) 5) а(а+2)-(а+3)^2

Упростите выражения 1) 5а(2-а)-(а+5)^2 2) 3с(с+2)-(с+3)^2 3) (а-6)^2-3а(4а-5) 4) (2х-3)^2-5х(6х-7) 5) а(а+2)-(а+3)^2
Гость
Ответ(ы) на вопрос:
Гость
10а-5а²-а²-10а-25=-(6а²+25)  3с²+6с-с²-6с-9=2с²-9  а²-12а+36-12а²+15а=3а-11а²+36  4х²-12х+9-30х²+35х=23х-26х²+9 а²+2а-а²-6а-9=-(4а+9)
Гость
1. [latex]5a(2-a)-(a+5)^2=\\10a-5a^2-(a^2+10a+25)=\\10a-5a^2-a^2-10a-25=\\-5a^2-a^2-25=\\-6a^2-25[/latex] 2. [latex]3c(c+2)-(c+3)^2=\\3c^2+6c-(c^2+6c+9)=\\3c^2+6c-c^2-6c-9=\\3c^2-c^2-9=\\2c^2-9[/latex] 3. [latex](a-6)^2-3a(4a-5)=\\a^2-12a+36-12a^2+15a=\\-11a^2-12a+15a+36=\\-11a^2+3a+36[/latex] 4. [latex](2x-3)^2-5x(6x-7)=\\4x^2-12x+9-30x^2+35x=\\-26x^2-12x+35x+9=\\-26x^2+23x+9[/latex] 5. [latex]a(a+2)-(a+3)^2=\\a^2+2a-(a^2+6a+9)=\\a^2+2a-a^2-6a-9=\\2a-6a-9=\\-4a-9[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы